Autonomic disorders in clinical practice - Micieli, Giuseppe; Hilz, Max-Josef; Cortelli, Pietro (Springer International Publishing, 2023)
The autonomic nervous system (ANS) is a subcomponent of the peripheral nervous system (PNS) and dysfunction of one or more subdivisions of the ANS, when accompanying other diseases, is linked to a worse prognosis of the latter. In some circumstances or when severe, dysfunction of ANS itself results in symptoms and disability. A myriad of factors can cause autonomic dysfunction and more than one can concur even in the same patient; due to the expansive nature of the ANS, patients can be affected by a wide range of conditions. Each chapter is characterized by a similar structure and is devoted to a different dysfunction. For each pathology, the book offers the essential information on mechanisms of action, treatments and outcomes. Written by experts in the research of these disorders, the volume addresses primarily Neurologists, but will be a useful tool also for Gastroenterologists, Ophthalmologists, Urologists, Cardiologists and Internal medicine specialists.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Autonomic Nervous System (ANS); Diagnostic approach to autonomic dysfunctions; Pathologies related to autonomic dysfunctions; Possible therapies; Symptoms